The Influence of Work Environment, Leadership, and Compensation on the Performance of Employees at the Ministry of Religious Affairs Office in Makassar City - Irfalasari Baso; Andi Jam’an; Agussalim Harrang (Eduvest - Journal of Universal Studies, 2024)
The purpose of this study was to determine and analyze the Influence of Work Environment, Leadership and Compensation on Employee Performance at the Makassar City Ministry of Religion Office. This type of research is quantitative research with a sample of 120 respondents using a questionnaire as a source of data collection, the analysis used is Multiple Linear Regression Analysis using the SPSS V.24 application. The results of the study indicate that: 1. Work Environment has a positive but not significant effect on employee performance, 2. Leadership has a positive and significant effect on employee performance, and 3. Compensation has a positive and significant effect on employee performance. With a confidence level of all variables of 95%.